Strategi Pengendalian Pencemaran Sungai Siak yang Berkelanjutan Menggunakan Pendekatan Multi Criteria Decision Making (MCDM) - Imam Suprayogi; Manyuk Fauzi; Alfian Alfian; Suprasman Suprasman; Nurdin Nurdin; Zulkifli Zulkifli (Universitas Riau, 2022)
The main objective of the research is to establish a sustainable Siak River pollution management strategy, in an effort to accelerate (quick win) the strategic policy of Siak River pollution management which is one of the National Strategic category rivers located in the Sumatra Region based on Presidential Decree No. 12 of 2012 concerning the Determination of the River Basin, because the Siak River has a very large function and role in regional and economic development both locally, regionally and nationally. The approach method used is Multi Criteria Decision Making (MCDM) with the selected method of Analytical Hierarchy Process (AHP). The primary data is in the form of questionnaire data with the aim of being assessed by experts (expert judgment) who are considered competent in assessing the processing of Siak River pollution. Seven respondents identified who have the potential and are representative to contribute to obtaining expert judgment recommendations consist of Universities represented by the University of Riau (UR), the Riau Province Environmental Agency (BLH), the Sumatran Ecoregion Development Control Center, Non-Governmental Organizations (NGO) Jikalahari, Center for Watershed Management (BPDAS) Indragiri Rokan. Regional Research and Development Agency for Riau Province and the River Basin Center (BWS) III Sumatra. The main results of the study stated that the Siak River water pollution control strategy using the AHP approach sequentially was to rearrange the spatial function, determine the pollution load capacity (DTBP), coordination of stakeholder synergies, program socialization and counseling, supervision and monitoring, law enforcement and development. Wastewater Treatment Plant (WTP).